Larvicidal activity of Hypoestes forskaolii (Vahl) R. Br root extracts against Anopheles gambiae Giless.s, Aedes aegypti L, and Culex quinquefasciatus Say - Sillo AJ; Makirita WE; Swai H; Chacha M (Dove Medical Press, 2019)
Albert J Sillo, Winisia E Makirita, Hulda Swai, Musa ChachaSchool of Life Sciences and Bio-Engineering, Nelson Mandela African Institution of Science and Technology, Arusha, TanzaniaAim: This study aimed to evaluate larvicidal activity of Hypoestes forskaolii R. Br root extract against 3rd instar Anopheles gambiae, Aedes aegypti, and Culex quinquefasciatus.Methods: A protocol developed by the World Health Organization was adopted, with minor modification using chloroform and methanol extracts with concentrations ranging from 25–750 μg/mL. Results: The H. forskaolii chloroform extract exhibited very high larvicidal activity after 72 hours of exposure, with LC50 2.0322, 3.8989, 6.0004 μg/mL against A. gambiae, A. aegypti, and C. quinquefasciatus, respectively.Conclusion: The larvicidal activity of H. forskaolii is reported for the first time in this paper. The effectiveness of H. forskaolii chloroform extract warrants further research to develop botanical mosquito repellants from this source.Keywords: Hypoestes forskaolii, LC50, Anopheles gambiae, Aedes aegypti, Culex quinquefasciatus